Dental erosion among children in an Istanbul public school - (:unkn) unknown (My University, 2005)
The aim of this study was to evaluate the prevalence, clinical manifestations, and etiology of dental erosion among children. A total of 153 healthy, 11-year-old children were sampled from a downtown public school in Istanbul, Turkey comprised of middle-class children. Data were obtained via: (1) dinical examination; (2) questionnaire; and (3) standardized data records. A new dental erosion index for children designed by O'Sullivan (2000) was used. Twenty-eight percent (N=43) of the children exhibited dental erosion. Of children who consumed orange juice, 32% showed erosion, while 40% who consumed carbonated beverages showed erosion. Of children who consumed fruit yogurt, 36% showed erosion. Of children who swam professionally in swimming pools, 60% showed erosion. Multiple regression analysis revealed no relationship between dental erosion and related erosive sources (P > .05).
Keywords: Female; Humans; Surveys and Questionnaires; Turkey; Prevalence; Male; Child; Hydrogen-Ion Concentration; Regression Analysis; Tooth Erosion; Fruit; Carbonated Beverages; Chlorine; Swimming Pools